Islamic Social Reporting (ISR), Sharia Supervisory Board (SSB), and Financial Performance: Empirical Evidence on Islamic Banks in the GCC Region - Iskandar, Rizkiana; Marlina, Lilis; Urna Fasihat, Dian (Publisher Cv. Inara, 2023)
This study aims to determine the relationship between the disclosure of Islamic social reporting (ISR), the Sharia Supervisory Board (SSB), and the financial performance of Islamic banks in the Gulf Cooperation Council (GCC) region. The Islamic banks that were the sample of the study totaled 25 banks spread across Bahrain, Kuwait, Qatar, Saudi Arabia and the United Arab Emirates with a sample period starting from 2013 to 2017. This research uses multiple regression testing and is complemented by content analysis. The results of content analysis show that the average level of ISR disclosure in Islamic banks in the GCC area is 56.53%. That is, the issues of social responsibility have not become a major concern for most Islamic banks. Furthermore, based on the test results, the ISR disclosure level proved to have a positive effect on financial performance. In addition, the existence of SSB in Islamic banks is also proven to have a positive association with financial performance which is proxied by return on average assets. These findings indicate that there are special things in Islamic banking such as disclosure of ISR and SSB that can have a good impact on the financial performance of Islamic banks.